If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (0) = 2x + 5 0 = 2x + 5 Reorder the terms: 0 = 5 + 2x Solving 0 = 5 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 0 + -2x = 5 + 2x + -2x Remove the zero: -2x = 5 + 2x + -2x Combine like terms: 2x + -2x = 0 -2x = 5 + 0 -2x = 5 Divide each side by '-2'. x = -2.5 Simplifying x = -2.5
| f(x)=3x^2-10x-8 | | 6x-11+2x=2+8x-13 | | 2ax-2ay+bx-by-cx+c= | | 2ax-2ay+1bx-1by-1cx+1cy= | | 4sin^2(2x)-7cos(2x)=2 | | t/4-1=11 | | t/4-1= | | 7y-11-5y+8=0 | | 4x-7=40x+20 | | -2x-6(0)=-14 | | -2(0)-6y=-14 | | 2(0)=x-7 | | 2y=(0)-7 | | 10(0)+10y=-30 | | 10x+10(0)=-30 | | -2(0)-2y=6 | | w=A[l] | | -2x-2(0)=6 | | -14(0)-4y+2=0 | | 0.000725=x^3 | | -14x-4(0)+2=0 | | -20=5x(-5+11)-50 | | 3(v-2)-5=-3(-7v+1)-4v | | xsquared=9/16 | | -14x-4y+2=0 | | 3(y+3)-7y=-15 | | 24x=-16x-5(-x+8)+30 | | 7x+6=-2y | | x.x-12=0 | | 10+x+16=4 | | 10+x+15=4 | | 5+16+9(x-6)=-18x |